NFAT5 Controls the Integrity of Epidermis - Muhammad, Khalid; Xavier, Delicia; Klein-Hessling, Stefan; Azeem, Muhammad; Rauschenberger, Tabea; Murti, Krisna; Avots, Andris; Goebeler, Matthias; Klein, Matthias; Bopp, Tobias; Sielaff, Malte; Tenzer, Stefan; et al. (Frontiers in Immunology, 2021)
The skin protects the human body against dehydration and harmful challenges. Keratinocytes (KCs) are the most abundant epidermal cells, and it is anticipated that KC-mediated transport of Na+ ions creates a physiological barrier of high osmolality against the external environment. Here, we studied the role of NFAT5, a transcription factor whose activity is controlled by osmotic stress in KCs. Cultured KCs from adult mice were found to secrete more than 300 proteins, and upon NFAT5 ablation, the secretion of several matrix proteinases, including metalloproteinase-3 (Mmp3) and kallikrein-related peptidase 7 (Klk7), was markedly enhanced. An increase in Mmp3 and Klk7 RNA levels was also detected in transcriptomes of Nfat5-/- KCs, along with increases of numerous members of the ‘Epidermal Differentiation Complex’ (EDC), such as small proline-rich (Sprr) and S100 proteins. NFAT5 and Mmp3 as well as NFAT5 and Klk7 are co-expressed in the basal KCs of fetal and adult epidermis but not in basal KCs of newborn (NB) mice. The poor NFAT5 expression in NB KCs is correlated with a strong increase in Mmp3 and Klk7 expression in KCs of NB mice. These data suggests that, along with the fragile epidermis of adult Nfat5-/- mice, NFAT5 keeps in check the expression of matrix proteases in epidermis. The NFAT5-mediated control of matrix proteases in epidermis contributes to the manifold changes in skin development in embryos before and during birth, and to the integrity of epidermis in adults.